Augmenter of liver regeneration: A key protein in liver regeneration and pathophysiology. Issue 8 (14th May 2018) - Gupta, Parul; Venugopal, Senthil Kumar
Abstract : Liver is constantly exposed to pathogens, viruses, chemicals, and toxins, and several of them cause injury, leading to the loss of liver mass and sometimes resulting in cirrhosis and cancer. Under physiological conditions, liver can regenerate if the loss of cells is less than the proliferation of hepatocytes. If the loss is more than the proliferation, the radical treatment available is liver transplantation. Due to this reason, the search for an alternative therapeutic agent has been the focus of liver research. Liver regeneration is regulated by several growth factors; one of the key factors is augmenter of liver regeneration (ALR). Involvement of ALR has been reported in crucial processes such as oxidative phosphorylation, maintenance of mitochondria and mitochondrial biogenesis, and regulation of autophagy and cell proliferation. Augmenter of liver regeneration has been observed to be involved in liver regeneration by not only overcoming cell cycle inhibition but by maintaining the stem cell pool as well. These observations have created curiosity regarding the possible role of ALR in maintenance of liver health. Thus, this review brings a concise presentation of the work done in areas exploring the role of ALR in normal liver physiology and in liver health maintenance by fighting liver diseases, such as liver failure, non‐alcoholic fatty liver disease/non‐alcoholic steatohepatitis, viral infections, cirrhosis, and hepatocellular carcinoma.